Git - gestão integrada de território na região do Conorte: implementação do projeto “Espírito Santo Sem Lixão" - Motta, Helaine do Amaral; Nunes, Marcus Antonius da Costa (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
New reflections on the paradigm of sustainability are needed to reach the solutions and advancement of structural and operational challenges , and it appears GIT - Integrated Management Planning . Integrated Territory Management - GIT emerges as proposed realignments of the goals of sustainability is shown as a path , an alternative to overcome the bottlenecks that are brought to the achievement of sustainable development . Objective in this context to search for information characterizing the GIT and its form of economic activity starting from x social assumptions and laws to ensure its activity. The methodology used to develop this , broke the literature from books , articles , magazines , internet and other materials that focus on the theme developed . Porting concludes that the economic, social, environmental complexity , and cultural territory of a demand for an integrated strategy , a tool such as GIT - Integrated Territory Management , which combines different actions of ministries , state and municipal governments and businesses society consolidating federal relations and making more efficient the action of the government in the territories not limited to attack specific problems more so with a larger area of action and the integration of all the spaces and actors involved.